Development of Canva Application-Based Motion Audio-Visual Media For The Creative Thinking Skills of Grade X Students at SMAN 1 Parigi Utara - Ani Sintiawati; Mohammad Jamhari; Lilies N Tangge (Jurnal Indonesia Sosial Teknologi, 2024)
Canva application-based motion audio-visual media is one form of learning media that can support 21st century learning. This study aims to develop and see the effectiveness of canva application-based motion audio-visual media on environmental pollution material on the ability to think creatively and science communication of grade X students at SMAN 1 North Parigi. The method used in this research is research and development (Research and Development) with 4D instructional design. This research was conducted on grade X students at SMAN 1 North Parigi totaling 48 students. The results of this study show that: (1) Canva application-based motion audio-visual media developed obtained a percentage of 86% of the very valid category and for practicality of media obtained a percentage of 87.5% of the very practical category for use in biology learning, (2) The effectiveness of motion audio-visual media based on the Canva application developed is very effective in improving students' creative thinking skills with effect size values 1.37 very large categories Based on the results of the development that has been carried out, Canva application-based motion audio-visual media can be a learning medium that can improve students' creative thinking skills in biology learning.